Teacher Educators' Use of Digital Tools and Needs for Digital Competence in Higher Education. Issue 4 (2nd October 2019) - Amhag, Lisbeth; Hellström, Lisa; Stigmar, Martin
Abstract: Based on a study at two Swedish universities, this article aimed to identify teacher educators' use of digital tools and subsequent need for digital competence in higher education. Methodically, a digital survey was distributed via e-mail to 405 teacher educators representing two faculties at the two universities; in total, 105 teacher educators responded. The survey included 16 questions, with closed- and open-ended varieties. Two theoretical foundations were used: the TPACK model and, as a complement, computer self-efficacy. Through analysis of self-reported use, competence, and need for professional training in digitalization in teaching, results show that teacher educators do not use digital tools primarily for pedagogical purposes. Thus, they need extensive pedagogical support in creating digital teaching. Further, teacher educators need to identify the pedagogical surplus value in their own teaching and learning context with digital tools to increase motivation for concrete, effective, and subject-oriented successful examples as presented by experienced teachers.